Juan's upon a time an iconological analysis on the development of Juan dela Cruz as an icon in media and advertising - Delos Reyes, Syra A.
This study was conducted to know the development of the icon Juan dela Cruz both then and now representing the Filipino identity in Media and Advertising. Also the researcher was aiming to know the representations of Filipino through the icon as a national symbol of every Filipino to whatever context the icon was used for. The researcher searched for different products and establishments that use the icon of Juan dela Cruz as part of their material for adverts. Fifteen subjects for analysis were identified. The study focused only to the visual component of these subjects that were associated to the icon itself. Using the visual approach of Iconology, these fifteen subjects were analyzed to generate meanings to know the development and representations of Filipinos. It was also part of the objectives of the researcher to identify common symbols and signs that can be found in the fifteen subjects for analysis that were incorporated to Juan dela Cruz. The concept of this visual approach, Iconology, provided the icon?s descriptions of its origin, convention, development and the apprehension of intrinsic meanings of the common symbols present. The result and discussion showed that Juan dela Cruz is a mixture of common Filipino symbols and these are the salakot, the barong trousers and the smile. Each of these symbols signifies certain meaning that has been apprehended using Iconology. It showed that salakot signify authority, barong signifies creativity, a trouser signifies a person?s status symbol, and the smile signifies enjoyment and happiness.